Broadband absorption of macro pyramid structure based flame retardant absorbers. (20th November 2022) - Sun, Hengda; Zhang, Ying; Wu, Yue; Zhao, Yue; Zhou, Ming; Liu, Lie; Tang, Shaolong; Ji, Guangbin
Highlights: A flame retardant and microwave absorbing carbon nanotube/ammonium polyphosphate composite is prepared by a simple process. The wave transparent flame retardant coating ensure the flame retardant and absorbing material not be ignited under open fire. The the maximum absorption bandwidth can reach 14.36 GHz by the pyramid structure. The designed pyramid structure can ensure the absorption bandwidth of 14 GHz at the incident angle within 60°. Abstract: Flame-retardant materials with good electromagnetic wave absorption play an increasingly important role in Over-the-Air (OTA) tests in microwave anechoic chambers. In this work, carbon nanotubes and ammonium polyphosphate (CNTs@APP) composite were prepared by crosslinking with the silane coupling agent (KH550). The flame retardancy is improved with the increase of APP. However, the microwave absorption performance (MAP) and processing difficulty changed greatly as well. Therefore, magnesium aluminum double-layer metal hydroxide (LDH) was obtained by coprecipitation method and processing into the coating, so as to realize flame retardancy which reaches the limiting oxygen index (LOI) of 24.8% and good MAP at the same time. Then, a high-frequency structure simulator (HFSS™) was used to simulate the pyramid model to realize the broadband absorption, and the optimal parameter range was obtained, that is, when the total height of the material is 40 mm, the height of the base accounts for 1/5–1/3, and the tangent of the half top angle is near 1/5, which result in the best MAP. Finally, the broadband absorption of 14.36 GHz (3.64–18 GHz) was realized when the base height is 1/3, and the broadband absorption of 14 GHz (4–18 GHz) can be realized under the condition of large-angle oblique incidence of 0°–60°. Graphical abstract: Based on the pyramid structure of flame retardant absorbers, the obtained samples possess both good flame retardancy and microwave absorption, which show great application prospects in the field of OTA test, broadband microwave absorption performance, and brodaband oblique incidence absorption. Image, graphical abstract